Dark triad constructs blend facets with heterogenous self-presentation tactic use profiles. (January 2022) - Hart, William; Breeden, Christopher J.; Lambert, Joshua; Kinrade, Charlotte
Abstract: A self-presentation framework for the Dark Triad (DT) constructs stipulates that each construct encompasses chronic patterns of tactical identity-maintenance behaviors. Research addressing this idea is scant, and the evidence has been limited to unidimensional measures of the DT constructs. Here, participants ( N = 309) completed multidimensional measures of the DT constructs and reported their past use of 12 self-presentation tactics. We speculated that each DT construct blends facets with distinguishable self-presentational profiles. Indeed, although each global DT construct showed substantial profile similarity across the 12 self-presentation tactics, the facets of each DT construct generally showed distinguishable self-presentation profiles. As such, self-presentational profiles germane to a global DT construct sometimes converged with and sometimes diverged from the profiles germane to facets of another DT construct. These findings supported a self-presentational framing of the DT constructs but suggest potential problems with reaching general conclusions on global profiles or the extent to which global DT constructs share a reliance on similar self-presentation tactics.